Kinematics of the crust in southern Tibet and Higher Himalayan Crystalline –a paleomagnetic approach - El Bay, Tachida; Appel, Erwin; Carosi, Rodolfo; Ding, Lin; Istvàn, Dunkl; Gloaguen, Richard; Montomoli, Chiara; Paudel, Lalu; Wauschkuhn, Bastian (Himalayan Journal of Sciences, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> DOI = 10.3126/hjs.v5i7.1233 Himalayan Journal of Sciences Vol.5(7) (Special Issue) 2008 p.22-23